Birth defects after use of antithyroid drugs in early pregnancy: a Swedish nationwide study. Issue 4 (October 2017) - Andersen, Stine Linding; Lönn, Stefan; Vestergaard, Peter; Törring, Ove
Abstract : Objective: Antithyroid drugs (ATDs) may have teratogenic effects, but more evidence is needed on the risk and types of birth defects after the use of methimazole (MMI) and propylthiouracil (PTU). This study aimed to evaluate the association between the use of ATDs in early pregnancy and birth defects. Design: Swedish nationwide register-based cohort study. Methods: The study included 684 340 children live-born in Sweden from 2006 to 2012. Exposure groups defined by maternal ATD use in early pregnancy were MMI ( n  = 162); PTU ( n  = 218); MMI and PTU ( n  = 66); ATD before or after, but not in pregnancy ( n  = 1551) and non-exposed (never ATD ( n  = 682 343)). Outcome was cumulative incidence of birth defects diagnosed before two years of age. Results: The cumulative incidence of birth defects was not significantly different in children exposed to MMI (6.8%, P  = 0.6) or PTU (6.4%, P  = 0.4) vs non-exposed (8.0%). For subtypes of birth defects, MMI was associated with an increased incidence of septal heart defects ( P  = 0.02). PTU was associated with ear ( P  = 0.005) and obstructive urinary system malformations ( P  = 0.006). A case of choanal atresia was observed after exposure to both MMI and PTU. The incidence of birth defects in children born to mothers who received ATD before or after, but not in pregnancy, was 8.8% and not significantly different from non-exposed ( P  = 0.3), MMI exposed ( P  = 0.4) or PTU exposed ( P  = 0.2). Conclusions: MMI and PTU were associated with subtypes of birth defects previously reported, but the frequency of ATD exposure in early pregnancy was low and severe malformations described in the MMI embryopathy were rarely observed.